Electroretinography as a non-invasive biomarker for early detection of cognitive impairment in older adults: A scoping review protocol - Isaiah Osei Duah Junior; Katelyn JeNay Houston; Danielle S. Rodriguez; Cassandra M. Germain (PLoS ONE, 2026)
Cognitive decline and dementia represent a growing global health challenge with an urgent need for accessible biomarkers to support early detection, monitoring, and timely intervention, particularly among marginalized populations who face persistent barriers to equitable access to specialized diagnostic and neurological care. Electroretinography (ERG), a non-invasive measure of retinal electrophysiological activity, has emerged as a potential visual biomarker given the retina’s structural and functional homology with the brain. Preliminary studies suggest associations between ERG abnormalities and cognitive impairment; however, the existing evidence base is limited and lacks sufficient consistency and integration to draw clear, definitive conclusions. The primary aim of this scoping review is to systematically characterize and synthesize existing evidence on the utility and efficacy of ERG as a visual biomarker of cognitive change and cognitive status in adults 50 years and over and identify research gaps. Specifically, the review will: (1) characterize study designs, populations, ERG modalities, parameters, and cognitive outcomes; (2) identify ERG components consistently associated with cognitive status or decline; (3) describe strategies for managing ophthalmic and systemic confounders; (4) locate longitudinal studies assessing prognostic or predictive utility; and (5) highlight methodological limitations, reporting gaps, and priority areas for future research. Following the Population–Concept–Context (PCC) framework, the review will include studies of older adults with cognitive impairment, or dementia, examining ERG modalities such as full-field, pattern, and multifocal ERG. All relevant and completed published studies in English language will be identified from MEDLINE (via PubMed), Embase, Web of Science, Scopus, PsycINFO, Google Scholar, Cochrane Central Register of Controlled Trials (CENTRAL) without date restrictions. The retrieved records will be managed in EndNote (version 2025), and in accordance with Covidence framework for scoping reviews, three reviewers will independently screen titles, abstracts, and full texts. Data will be charted on study characteristics, ERG parameters, cognitive outcomes, and ERG-cognitive status associations. Collectively, this synthesis will provide clinicians and researchers with consolidated evidence on ERG–cognition relationships, clarify whether the evidence base supports further systematic review or meta-analysis, and generate methodological recommendations for future studies.